The absolute lymphocyte/monocyte ratio recovery during ABVD treatment cycles is not significantly impacted by the use of myeloid growth factors and predicts clinical outcomes in classical Hodgkin lymphoma regardless of their use - Kaufman GP (Dove Medical Press, 2014)
Gregory P Kaufman,1 Kay M Ristow,1,2 Svetomir N Markovic,1,2 Luis F Porrata1,2 1Department of Internal Medicine, 2Division of Hematology, Mayo Clinic, Rochester, MN, USA Abstract: Risk stratification of patients with classical Hodgkin lymphoma (cHL) remains suboptimal. The ratio of the absolute lymphocyte count (ALC) to absolute monocyte count (AMC) both at diagnosis and during subsequent recovery from serial cycles of chemotherapy predicts survival in cHL, and possesses advantages over other commonly used prognostic markers. Myeloid growth factors (MGFs), while not strongly recommended for use in adriamycin, bleomycin, vinblastine, and dacarbazine (ABVD) treatment cycles, are not uncommonly used to prevent the negative consequences of neutropenia. The effect that MGFs have on the ALC/AMC ratio during ABVD treatment cycles, if any, remains unclear. We retrospectively evaluated 208 patients with cHL, who were diagnosed, treated, and followed at Mayo Clinic Rochester between 1990 and 2014, and who had quantifiable records for the use of MGFs during ABVD treatment cycles. Having an ALC/AMC ratio <1.1 during all treatment cycles was confirmed as being a negative predictor of overall and progression free survival (hazard ratio [HR] 0.06, 95% confidence interval [CI] 0.03–0.14 and HR 0.08, 95% CI 0.04–0.17, respectively). Data on both the ALC/AMC ratio and use of MGFs were available for 1,979 half treatment cycles. When stratified to whether or not MGFs were given, the change in the ALC/AMC ratio as compared to the prior half cycle was found to be statistically insignificant (P=0.3445). No survival advantage was found with the administration of MGFs in any cycle of therapy (log rank P=0.5713). Our data validate the prognostic significance of having an ALC/AMC ratio of ≥1.1 regardless of the use of MGFs. Keywords: myeloid growth factors, classical Hodgkin lymphoma, survival ALC/AMC ratio, ABVD chemotherapy